Software-Defined Caching: Managing Caches in Multi-Tenant Data Centers - Stefanovici, Ioan; Thereska, Eno; O'Shea, Greg; Schroeder, Bianca; Ballani, Hitesh; Karagiannis, Thomas; Rowstron, Ant; Talpey, Tom (ACM Symposium on Cloud Computing (SOCC) 2015, 2015)
In data centers, caches work both to provide low IO latencies and to reduce the load on the back-end network and storage. But they are not designed for multi-tenancy; system-level caches today cannot be configured to match tenant or provider objectives. Exacerbating the problemis the increasing number of un-coordinated caches on the IO data plane. The lack of global visibility on the control plane to coordinate this distributed set of caches leads to inefficiencies, increasing cloud provider cost. We present Moirai, a tenant- and workload-aware system that allows data center providers to control their distributed caching infrastructure. Moirai can help ease the management of the cache infrastructure and achieve various objectives, such as improving overall resource utilization or providing tenant isolation and QoS guarantees, as we show through several use cases. A key benefit of Moirai is that it is transparent to applications or VMs deployed in data centers. Our prototype runs unmodified OSes and databases, providing immediate benefit to existing applications.